Badibanga 2016. Mbororo, Invasion of a Nation - Taluah, Reginald Asangba (AAeO - Afrikanistik-Aegyptologie-Online, 2018)
Arthur Cimwanga Badibanga 2016. Mbororo, Invasion of a Nation. LAP Lambert Academic Publishing - ISBN: 978-3-659-86375-2 ; 19,19 €